Analisis Implementasi Good Governance pada Survey e-Government PBB Tahun 2022 - Rustiawan, Mulyana; Rachmawati, Ike (Jurnal Pendidikan Siber Nusantara, 2024)
Good Governance and e-Government are two things that represent the desires of society, not only the local Indonesian community but also become the desire of world society, namely the desire to manage the life of the nation, state and society at the highest level. This study uses 9 Principles of Good Governance as an analytical tool to ensure the principles of Good Governance are part of the implementation of e-Government as stated in the 2022 UN Member States Questionnaire released by the UN Department of Economic and Social Affairs (UNDESA). The results of the analysis show that of a number of e-Government survey dimensions there are important points that are in line with the principles of implementing Good Governance.